Answer:
see explanation
Step-by-step explanation:
The n th term of an AP is
[tex]a_{n}[/tex] = a₁ + (n - 1)d
where a₁ is the first term and d the common difference
(1)
Given a₁ = 5 and a₄ = [tex]\frac{9}{2}[/tex] , then
5 + 3d = [tex]\frac{9}{2}[/tex] ( subtract 5 from both sides )
3d = - [tex]\frac{1}{2}[/tex] ( divide both sides by 3 )
d = - [tex]\frac{1}{6}[/tex]
add - [tex]\frac{1}{6}[/tex] to each term
5, [tex]\frac{29}{6}[/tex], [tex]\frac{14}{3}[/tex], [tex]\frac{9}{2}[/tex]
(2)
Given a₁ = - 4 and a₆ = 6, then
- 4 + 5d = 6 ( add 4 to both sides )
5d = 10 ( divide both sides by 5 )
d = 2
Add 2 to each term
- 4, -2, 0, 2, 4, 6
(3)
Given a₂ = 38 and a₆ = - 22, then
a₁ + d = 38 → (1)
a₁ + 5d = - 22 → (2)
Subtract (1) from (2) term by term
4d = - 60 ( divide both sides by 4 )
d = - 15
Substitute d = - 15 into (1)
a₁ - 15 = 38 ( add 15 to both sides )
a₁ = 53
Thus
53, 38, 8, - 7, - 22